Electronic Word of Mouth sebagai Determinan Niat Beli Produk Skincare: Studi Kasus pada Generasi Z di Era Digital - Nameto, Melati Putri; Wardi, Yunia (SAFE-Network, 2025)
This study aims to analyze the effect of Electronic Word of Mouth (E-WOM) on E-Purchase Intention with E-Consumer Trust as a mediating variable among Generation Z consumers of Skintific skincare products. Employing a quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM), data were collected through questionnaires distributed to respondents actively engaged in online shopping. The research reveal that E-WOM has a positive and significant effect on both E-Purchase Intention and E-Consumer Trust. However, E-Consumer Trust does not significantly influence E-Purchase Intention, nor does it mediate the relationship between E-WOM and E-Purchase Intention. These results highlight the crucial role of E-WOM in directly shaping digital consumers’ purchasing behavior, while consumer trust serves more as a long-term foundational factor rather than an immediate driver of purchase intent. This research contributes theoretically to the digital marketing literature and offers practical implications for experience-based promotional strategies.